Biotherapeutic potential of different fractions of cell-free supernatants from Lacticaseibacillus rhamnosus against Pseudomonas aeruginosa - Bianchi, Marta; Kaya, Esingül; Logiudice, Viviana; Maisetta, Giuseppantonio; Curtis, Aaron; Kavanagh, Kevin; Batoni, Giovanna; Esin, Semih (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionDue to their content of multiple antimicrobial bioactive substances, cell-free supernatants (CFS) from lactic acid bacteria are emerging as novel antimicrobials. We have previously demonstrated that CFS from Lacticaseibacillus rhamnosus exert strong antibacterial and antibiofilm activity against Pseudomonas aeruginosa isolated from chronic infections. Herein, we sought to identify the CFS fraction(s) responsible for such activities and characterize the same CFS in terms of immunomodulatory properties and protein content.MethodsA P. aeruginosa clinical isolate was used in the study. CFS fractions were obtained by 3 kDa cut-off size-exclusion filtration. The antibacterial and antibiofilm activity of unfractionated and fractionated CFS was tested on planktonic and biofilm-associated P. aeruginosa using colony-forming unit enumeration, crystal violet staining, and confocal microscopy. Label-free qualitative proteomic was performed using a shotgun approach with mass spectrometry to characterize the protein content of the CFS. Additionally, the immunomodulatory effects of the CFS were evaluated on human peripheral blood mononuclear cells (PBMC) stimulated with P. aeruginosa lipopolysaccharide (LPS) or biofilm-derived P. aeruginosa cells.ResultsBoth antibacterial and antibiofilm activities were mainly, but not exclusively, ascribed to the low molecular weight CFS fraction (≤ 3 kDa), which contained most of the lactic acid, suggesting a major role of this component in the antimicrobial effect of CFS. The > 3 kDa fraction alone was almost inactive but displayed a synergistic antibacterial effect when reconstituted with the ≤ 3 kDa fraction. Proteomics analysis of CFS revealed the presence of cell wall hydrolases, suggesting that these enzymes might contribute to the antibacterial activity observed in the reconstituted fractions. Following 6 h stimulation of PBMC with LPS or biofilm-derived P. aeruginosa, a marked anti-inflammatory effect was exhibited by unfractionated CFS as well as ≤ 3kDa fraction at non-toxic concentrations, while the > 3kDa fraction was found to induce the production of IL-6, TNF-α, and to a lesser extent of IL-10.ConclusionThe obtained results support that, due to their multiple antimicrobial and anti-inflammatory effects, probiotic metabolites might represent a promising strategy for the prevention and/or treatment of chronic infections with an intense inflammatory response such as those caused by P. aeruginosa.